Third Party-Certifications in Aquaculture - Emily H. Roan; Joshua Patterson; Matthew DiMaggio; Roy Yanong (EDIS)
This publication provides information on common third-party certification programs for aquaculture products, mostly those intended for human consumption. The goal of this document is to increase consumer awareness and understanding of what commonly observed third-party certification labels signify. Includes some discussion of certification programs for ornamentals and baitfish.